Tinjauan Fiqih Muamalah terhadap Praktik Pinjam Pakai di Desa Sayur Matinggi Kecamatan Sayur Matinggi Kabupaten Tapanuli Selatan - Hardani, Rahmad Hardani; Rofiq, Mahbub Ainur Rofiq (IAIN Langsa, 2023)
The practice of borrowing is a pawn practice that develops in people's lives, especially in Sayur Matinggi Village, Sayur Matinggi District, South Tapanuli Regency. In the practice of borrowing and using rice field owners will pledge their fields to get loans from capital owners. In fact, in the practice of borrowing and using there are still frequent problems. The problem of default and the use of pawn objects, which are still problematic for Islamic scholars, are a series of problems found in the practice of borrowing. This research is empirical legal research using a qualitative approach. This study will analyze and identify the problems found in the practice of lending and using in Sayur Matinggi village, Sayur Matinggi District, South Tapanuli Regency, the perspective of muamalah fiqh. The results showed that the validity of lending practices in Sayur Matinggi Village depends on the use of collateral by the second party. As for the views of madzhab scholars regarding the use of collateral, there are differences of opinion. Some scholars allow it on condition of approval, while others forbid it because of the potential for usury. The practice of lending and using is considered valid if there is a clearly written agreement, including loan terms, and transparency in the use of collateral. However, if there is a default, the agreement becomes void according to the provisions of the muamalah fiqh.